2016
DOI: 10.1038/srep30244
|View full text |Cite
|
Sign up to set email alerts
|

PACSIN2 polymorphism is associated with thiopurine-induced hematological toxicity in children with acute lymphoblastic leukaemia undergoing maintenance therapy

Abstract: Adequate maintenance therapy for childhood acute lymphoblastic leukemia (ALL), with 6-mercaptopurine as an essential component, is necessary for retaining durable remission. Interruptions or discontinuations of the therapy due to drug-related toxicities, which can be life threatening, may result in an increased risk of relapse. In this retrospective study including 305 paediatric ALL patients undergoing maintenance therapy, we systematically investigated the individual and combined effects of genetic variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
1
18
0
1
Order By: Relevance
“…For ALL patients, an increased incidence of grade III/IV stomatitis and diarrhea during consolidation therapy in patients with variant T alleles could be confirmed, as previously reported [14]. Moreover, a trend for an association between PACSIN2 variants and severe HEM toxicities during maintenance therapy was found, confirming previously described data [34]. The results showed in this study are encouraging toward a significant effect of PAC-SIN2 variant on chemotherapy-induced adverse events occurrence although they are limited by the small number of individuals with already available clinical data.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For ALL patients, an increased incidence of grade III/IV stomatitis and diarrhea during consolidation therapy in patients with variant T alleles could be confirmed, as previously reported [14]. Moreover, a trend for an association between PACSIN2 variants and severe HEM toxicities during maintenance therapy was found, confirming previously described data [34]. The results showed in this study are encouraging toward a significant effect of PAC-SIN2 variant on chemotherapy-induced adverse events occurrence although they are limited by the small number of individuals with already available clinical data.…”
Section: Discussionsupporting
confidence: 89%
“…It is therefore likely that the genetic effect of PACSIN2 rs2413739 on TPMT activity in ALL children emerges only under more physiological conditions, such as those found during the maintenance phase characterized by low-doses MTX and quite normal production and life cycle of RBC. A recent study has associated the PACSIN2 rs2413739 genotypes with the incidence of HEM toxicities during maintenance, this finding further supports the effect of this polymorphism in thiopurine biotransformation during this phase [34]. It is possible that the putative weak genetic influence of PACSIN2 varies with patient age and becomes more evident in younger patients because of higher measurable TPMT activity [35].…”
Section: Discussionmentioning
confidence: 55%
“…It has been demonstrated in vitro that individuals with the PACSIN2 rs2413739 CC genotype exhibited higher TPMT activities compared with carriers of other PACSIN2 variants (29). It was also confirmed that PACSIN2 rs2413739 CC-positive patients with ALL exhibited a lower incidence of gastrointestinal and hematological mercaptopurine toxicities in contrast to the ones with 25 CT and TT allele (29,30).…”
Section: Discussionmentioning
confidence: 76%
“…The same proportion of individuals with ultra-high TPMT activity was determined in a cohort of healthy Caucasian people (25)(26)(27)(28). Several candidate factors, including variable number tandem repeats (VNTRs) identified on the TPMT gene promotor, protein kinase C, casein kinase substrate in neurons 2 (PACSIN2) and SAM, responsible for the upregulation of TPMT activity were identified by the previous studies (25,26,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…When this PhD project started, a few studies concerning varying enzyme activity or the connection between varying genotypes and adverse reactions in other thiopurine metabolizing enzymes had been published. Throughout these years, the complexity of thiopurine metabolism has been more extensive with reports of several polymorphisms within the metabolism of thiopurines (ITPA [166,167], HGPRT [142,168], IMPDH [168][169][170], XO [60,171], GST [172][173][174], GMPS [168], Rac1 [175], NT5C2 [176,177], PACSIN2 [178], genes in the mismatch repair system (MMR) [179], folate cycle [152][153][154] and transporters [56,175,[180][181][182]) and recently, pharmacogenetic testing of NUDT15, whose variants are more common in Asian populations, has been implemented in the guidelines of the Clinical Pharmacogenetics Implementation Consortium (CPIC) for thiopurine treatment [19,183] . Otherwise, so far, no other polymorphism has had the same extensive effect on thiopurine treatment as the genetic variants of TPMT.…”
Section: Discrepancies and Factors Influencing The Activitymentioning
confidence: 99%